HUBUNGAN TINGKAT MOTIVASI PENGAWAS MINUM OBAT DENGAN PENCAPAIAN ANGKA KONVERSI BTA PADA PASIEN TB PARU - Hidayah, Mulyani (JURNAL MEDIA KESEHATAN, 2014)
Tubercle Bacillus disease in Indonesia is ranked number 5 in the world. One of the factors that affect the achievement of the conversion rate is PMO motivation in monitoring TB patients during TB medication ingestion. The purpose of this study was to determine the relationship between the level of supervisors’ motivation to take medication with achieving a conversion rate of sputum smear examination of TB patients in the Sukamerindu community health center of Bengkulu Year 2014 This research was a descriptive cross using sectional analytic sample approach that obtained through purposive sampling amounted 37 patients with pulmonary TB and type of data that collected was primary data. Analysis technique that used in this study was the chi-square statistical test, presented in table form and narrative. The results showed that the majority of respondents have low motivation (75.7%) more than the majority achieving of conversion rate (56.8%). Chi Square Test results showed that there was relationship between supervisory level of motivation to take medication and conversion rate achievement of sputum smear examination of pulmonary TB patients (p = 0.024 (<α = 0.05). It is Expected that health workers (nurses and doctors) to be more discipline in monitoring eradication program of infectious diseases, especially pulmonary TB and Drug Supervisory